Immune Characteristics in Biliary Atresia Based on Immune Genes and Immune Cell Infiltration - Yang, Chenyu; Xing, Huiwu; Tan, Bingqian; Zhang, Mingman (Frontiers in Pediatrics, 2022)
Background Biliary atresia (BA) is a serious biliary disease in infancy. Jaundice is the most visual and prominent symptom, and it mainly involves bile duct cells leading to the loss of intrahepatic and extrahepatic bile ducts. If left untreated, it will eventually progress to liver cirrhosis. The pathogenesis of BA is not clear, and it is now generally accepted that BA is an autoimmune disease. However, few studies have revealed the infiltration of immune cells in the liver of BA from a global perspective. We used liver tissue sequencing data to predict the infiltration and relative content of immune cells in BA. Methods The BA datasets GSE46960, GSE15235, and GSE84044, and patient information were downloaded from the Gene Expression Omnibus (GEO) database. After batch normalization, the differentially expressed immune genes (DE-IGs) in BA liver, normal liver, and hepatitis B liver were analyzed with the cut-off value of |log2fold change (log2FC)| >1 and false discovery rate (FDR) <0.05. CIBERSORT software was used to predict the proportions of 22 immune cells in all samples of the datasets. Results 73 DE-IGs have been screened out between BA and normal tissue; among them, 20 genes were highly expressed and another 53 were expressed at a low level. A total of 30 DE-IGs existed between inflammation and fibrosis livers of BA, and all of them were expressed at low levels in fibrosis livers of BA. In GO term analysis, these DE-IGs were mainly associated with the MHC protein complex, cytokine, chemokine activity, and MHC-II receptor activity. In KEGG pathway analysis, the DE-IGs were mainly enriched in pathways of Th1 and Th2 cell differentiation, Th17 cell differentiation, IL-17 signaling pathway, Toll–like receptor signaling pathway, TNF signaling pathway, and autoimmune diseases. There were significant differences in immune infiltration among different pathological types of BA, and there were also obvious differences in immune infiltration of hepatitis B as a disease control of BA. Conclusion Based on immune genes and immune cell infiltration, this study reveals the immune characteristics of BA from a global point of view, which provides a new perspective for understanding the pathogenesis of BA and provides a direction for the diagnosis and treatment of BA.